Germline and somatic alterations in NBN and their putative impact on the pathogenesis of malignant neoplasms - O. M. Krivtsova; D. D. Ozerova; N. L. Lazarevich (Успехи молекулярной онкологии, 2024)
Disruption of mechanisms that maintain genome stability is an essential factor of tumor progression. Accordingly, predisposition to the development of neoplasms is often associated with germline mutations in genes involved in DNA damage detection and repair. At the same time, impairment of DNA repair systems may be a predictor of antitumor treatment efficacy while overexpression of genes involved in DNA repair is a frequent event in various types of malignancies that can lead to development of tumor cells’ resistance to chemo- and radiotherapy. NBN (nibrin) gene encodes the subunit of the MRN complex which acts as a sensor of double-strand DNA breaks and participates in their repair by homologous recombination. Germline variants in NBN which are associated with increased risk of tumor development are generally represented by frameshift mutations that lead to the synthesis of truncated protein as well as by nonsense and some missense mutations which occur in functionally significant domains. These germline mutations result in partial loss of nibrin function and in increased frequency of spontaneous and induced chromosomal aberrations in the cells of the carriers. On the contrary, amplification of NBN locus is a predominant type of somatic mutations affecting this gene, which indicates a dual role of NBN protein in tumor progression. The results of several studies demonstrate the influence of NBN expression level and its mutational status on anti-tumor drug resistance in particular types of tumor cells and on the survival rate of patients. These data indicate that an in-depth study of different variants and their functional significance is necessary since NBN status may be essential for the choice of treatment tactics for some types of tumors.